Constitutional consequences of the ontological assimilation (or not) between crimes and tax offenses. Analysis based on the jurisprudence of the Supreme Court of Justice of the Argentine Republic - Álvarez Echagüe, Juan Manuel (2021)
In this work I continued to develop, expand and review concepts and ideas about the legal nature of infractions and crimes in tax matters, describing the various positions (theories) that exist on the subject, maintaining that from my point of view they have identity ontological, with merely quantitative differences, and that, as a consequence of assimilation, there is a single set of governing principles, which are the constitutional and legal principles of criminal law, ruling out the possibility of talking about the existence of a set of own principles of sanctioning administrative law. All this with the support of the jurisprudence of the Supreme Court of the Argentine Nation.